Approximation of Model Predictive Control Laws for Polynomial Systems. Issue 5 (31st March 2014) - Canale, M.; Cerone, V.; Piga, D.; Regruto, D.
Abstract A fast implementation of a given predictive controller for polynomial systems is introduced by approximating the optimal control law with a piecewise constant function defined over a hyper‐cube partition of the system state space. Such a state‐space partition is computed in order to guarantee stability, an a priori fixed trajectory error as well as input and state constraints fulfilment. The presented approximation procedure is achieved by solving a set of nonconvex polynomial optimization problems, whose approximate solutions are computed by means of semidefinite relaxation techniques for semialgebraic problems.